THE EFFECT OF PROMOTION THROUGH INSTAGRAM AND SOCIAL MEDIA MARKETING ON CONSUMER BUYING INTERESTS AT COFFEE TRIP - Dian Rahayu; Puji Isyanto; Neni Sumarni (Journal Of Resource Management, Economics And Business, 2024)
Purpose: This research aims to investigate the impact of Instagram promotions on consumer buying interest specifically within the context of coffee trips. The study seeks to understand how social media marketing can effectively attract consumers and enhance their purchasing decisions. Research Methodology: The research utilizes a quantitative approach, employing a non-probability sampling technique. Specifically, a purposive sampling method was used to select respondents who are active Instagram users and have shown interest in coffee-related content. A total of 91 respondents participated in the study, providing data through structured questionnaires. Results: The analysis of the collected data reveals that Instagram promotions significantly and positively influence consumer buying interest. This suggests that effective marketing strategies on social media can lead to increased consumer engagement and purchasing behavior in the coffee sector. Limitations: The study is constrained by its focus on a specific group of Instagram users, which may limit the generalizability of the findings. Additionally, the research does not account for other factors that may influence consumer buying behavior outside of social media marketing. Contribution: This research contributes to the broader understanding of social media marketing's role in consumer behavior. It highlights the effectiveness of Instagram as a promotional platform in the coffee industry, providing insights for marketers seeking to leverage social media to enhance consumer interest and drive sales.